Pediatric Scleritis: An Update. (2nd January 2023) - Tarsia, Maria; Gaggiano, Carla; Gessaroli, Elisa; Grosso, Salvatore; Tosi, Gian Marco; Frediani, Bruno; Cantarini, Luca; Fabiani, Claudia
ABSTRACT: Posterior idiopathic scleritis is the most common type of scleritis observed in childhood. Nevertheless, anterior and even necrotizing inflammatory scleritis may occur as well. Although less frequently than in the adult population, scleral inflammation can be associated with systemic disorders, which should be promptly recognized and treated to avoid both ocular and systemic complications. Hence, a multidisciplinary diagnostic work-up should be performed to rule out primarily infectious and autoimmune causes, such as viral and bacterial infections, anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis, pediatric sarcoidosis, Behçet's disease and HLA-B27-associated diseases. Treatment of scleritis should aim to control ocular inflammation, relieve symptoms and prevent relapses, to avoid complications, preserve visual acuity and improve the child's quality of life. It should be tailored to the patient, considering the type and severity of scleritis, the possible identification of an infectious cause or the presence of an associated rheumatologic condition.